Perancangan Modul Interaktif Menggunakan Aplikasi Articulate Storyline Pada PT BFI Finance Indonesia Tbk - Aisyah, Euis Sitinur; pahad, Rifat syauqi; Syahdarani, Syali Alivia (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
M-Beat (Mobile BFI Edustream and Training Application) is a BFI Finance e-Learning platform dedicated to employee learning and training. One of the features of the M-Beat is the Interactive feature which is an interactive module. However, currently, only a few modules are already interactive. This is not yet fully effective because the modules still in PDF form are monotonous. Therefore, it is necessary to build interactive modules on other modules that are still in PDF form. In creating this interactive module, researchers used PowerPoint for storyboard creation, and Articulate Storyline 360 to make the module interactive.